Pendidikan Anak Dalam Keluarga - Agustang; Arifuddin Ahmad; Erwin Hafid (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The aim of this research is to describe and analyze children's education in the family. This research method uses qualitative methods with the type of library research (Library research). Data collected through library research consisting of source data (primary) in the form of books related to the education of children in families. The results of this study indicate that, the education of children in the family is education in the family which has an important influence on educating children. this has a positive influence where the family environment gives encouragement or provides motivation and stimulation to accept, understand, believe, and practice Islamic teachings. in the family should be able to realize the goals of Islamic religious education. The birth of a child in a family apart from providing its own happiness also creates a new task for both parents, the responsibility for their care and education. Islam views children as a mandate from Allah that must be properly cared for from anything that is harmful both physically and spiritually.